Knowledge on child rights among private and government school teachers, Pokhara, Kaski district - Sah, Indu; Soti, Harikala; Paudyal, Laxmi; Gautam, Nitu Singh (Journal of Gandaki Medical College-Nepal, 2022)
Introduction: Children play vital role to the nation’s present and its future. The healthy and educated child of today is the intelligent and active citizen of tomorrow. Hence, the objective of our study was to assess the level of knowledge regarding child rights among teachers, compare the knowledge about child rights in context of private and government school, measure the association between knowledge regarding child rights with selected demographic variables.Methods: This is a cross-sectional comparative study conducted among 200 school teachers 100 each from four government and three private schools of Pokhara using purposive sampling method. Data was collected from November 1 to December 1, 2021. Structured self-administered questionnaire tool on knowledge regarding child rights was prepared by the researcher herself. The data were collected by self-administered tool by researcher herself within 30 minutes. The quantitative data was analyzed using statistical package for social sciences version 20.0 descriptive statistics and non-parametric test were used for analyzing knowledge and association. P-value of